Understanding digital marketing : a complete guide to engaging customers and implementing successful digital campaigns - Ryan, Damian (London : Kogan Page, 2021)
A practical, no-nonsense guide to digital marketing, giving readers all the information they need to feel confident engaging consumers online and implementing digital campaigns.
1. Introduction: Digital transformation -- 2. Digital marketing strategy setting -- 3. Being online: Welcoming the world -- 4. Search: Being found online -- 5. Email marketing -- 6. Mobile marketing -- 7. Social media -- 8. Content marketing and native content -- 9. Programmatic marketing -- 10. Performance marketing -- 11. How to form meaningful insights from data.
Keywords: Marketing; Internet marketing; Social media; Strategic planning; digitaalinen markkinointi; markkinointiviestintä; markkinointi; verkkomainonta; sosiaalinen media; mobiilimarkkinointi; strategiat; suunnittelu